Humus composition and humification degree of humic acids of alpine meadow soils in the northeastern part of the Qinghai–Tibet Plateau. Issue 1 (2nd January 2019) - Han, Beibei; Kitamura, Kyoko; Hirota, Mitsuru; Shen, Haihua; Tang, Yanhong; Suzuki, Takeshi; Fujitake, Nobuhide
ABSTRACT: The characteristics of humus composition are important for understanding the mechanism of carbon storage in the Qinghai–Tibet Plateau. The aim of this study was to characterize the quality of soil organic matter (SOM) in this region. Soil samples from four soil profiles in fenced study sites in the alpine grassland were collected at altitudes of 4200, 4000, 3800, and 3400 m, along the southwest facing slope in the Qilian Mountains. The humus composition and humification degree of the humic acid (HA) were determined by two methods: (1) extraction with 0.5% sodium hydroxide (NaOH) followed by 0.1 M sodium pyrophosphate (Na4 P2 O7 ) (OH-PP method); and (2) treating once with 0.1 M hydrochloric acid (HCl) followed by extracting with 0.5% NaOH (Cl-OH method). Physico-chemical analysis revealed higher exchangeable cation content and higher base saturation ratios could be related to slightly acidic to neutral soils, which could be regarded as calcium (Ca)-rich soils. The amounts of combined-form HAs obtained by HCl pretreatment (HACl – HAOH ; ∆HACl ) were remarkably higher than those extracted with Na4 P2 O7 (HAPP ), indicating that the combined form of HAs is mainly Ca. In addition, the proportion of HAPP in the total HAs extracted with both NaOH and Na4 P2 O7 (HAOH + HAPP ) obtained in the OH-PP method increased with soil depth and decreasing elevation, indicating that HAs associated with aluminum (Al) and iron (Fe) were distinguished in the subsoils of lower elevation. Therefore, the formation of the organo-mineral complex may contribute to stabilizing SOM in the Qinghai–Tibet Plateau. Moreover, Type A-HA with the highest degree of humification was obtained from the deeper horizons with the Cl-OH method and almost all horizons by extraction with Na4 P2 O7 in the OH-PP method. Further studies using various spectroscopic analyses are necessary to elucidate the chemical properties of SOM in this region.